PENGARUH PROMOSI SOSIAL MEDIA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PADA TOMORO COFFEE MANGUNJAYA TAMBUN SELATAN - Allpiah, Riki Nur; Supriyanto, Supriyanto; Wijayanti, Murti; Siahaan, Matdio (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the influence of social media promotion and product quality on customer loyalty at Tomoro Coffee Mangunjaya, Tambun Selatan. The research method used is quantitative with an associative approach. The sample consisted of 105 respondents who are customers of Tomoro Coffee. Data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that social media promotion has a positive and significant effect on customer loyalty, with a t-value of 11.991. Product quality also has a positive and significant effect, with a t-value of 7.541. Simultaneously, social media promotion and product quality significantly affect customer loyalty, with an F-value of 655.166. The coefficient of determination (R²) is 0.926, indicating that 92.6% of the variation in customer loyalty is explained by the two independent variables. This study highlights the importance of effective promotion and consistent product quality in building customer loyalty.